The essential guide to HTML5 using games to learn HTML5 and JavaScript - Meyer, Jeanine (Apress, 2022)
Gain a deep, practical knowledge of the basic tools used for webpages: hypertext markup language (HTML5), cascading style sheets (CSS), and JavaScript. This updated version includes new and improved games and exercises, and will serve total beginners as well as people with some programming language experience, but not familiar with the combination of HTML, CSS, and JavaScript. You'll begin at an introductory level with the focus on technical features as well as programming techniques. Each chapter features a familiar game such as Rock-Paper-Scissors, Craps, Memory, and Blackjack or generic examples such as working with Mazes. Other projects include constructing and saving a maze; a basic word guessing game; ballistic games (Cannonball and Slingshot); a quiz requiring items to be put in order; and an animation demonstration featuring a ball, photo or video clip bouncing within a rectangle. The Appendix contains examples of advanced techniques such as Scalar Vector Graphics programs displaying the HTML5 Logo and a cartoon figure, each of which can be changed dynamically, and mathematical techniques for calculating if a move crosses a line and re-adjusting an arrangement of circles and arrows. The exposition on each example in the chapters and the Appendix includes screen shots and tables revealing the structure of the program and statement by statement explanation of code. The book also contains suggestions for using the concepts and techniques to build your own programs. If you follow through with your own ideas, you will develop solid programming skills for building websites and for learning other programming languages, including the next version of HTML and current and future JavaScript frameworks, libraries and tools.
Includes index
Keywords: HTML (Document markup language); JavaScript (Computer program language); Web sites -- Design; HTML (Langage de balisage); JavaScript (Langage de programmation); Sites Web; Conception; HTML; Web sites; Design